2019
DOI: 10.1088/2050-6120/ab1985
|View full text |Cite
|
Sign up to set email alerts
|

Protein fibrillogenesis model tracked by its intrinsic time-resolved emission spectra

Abstract: The excited-state kinetics of the fluorescence of tyrosine in a de novo protein fibrillogenesis model was investigated as a potential tool for monitoring protein fibre formation and complexation with glucose (glycation). In stark contrast to insulin the time-resolved emission spectra (TRES) recorded over the period of 700 hours in buffered solutions of the model with and without glucose revealed no apparent changes in Tyr fluorescence responses. This indicates the stability of the model and provides a measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It has been found that hexameric insulin under physiological conditions undergoes conformational changes throughout 700 hours. This was further supported by similar assembly kinetics of a model fibrillar protein 24 suggesting a generic mechanism and that the sufficient sensitivity of TERS to monitor protein stability for medicinal purposes.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…It has been found that hexameric insulin under physiological conditions undergoes conformational changes throughout 700 hours. This was further supported by similar assembly kinetics of a model fibrillar protein 24 suggesting a generic mechanism and that the sufficient sensitivity of TERS to monitor protein stability for medicinal purposes.…”
Section: Introductionmentioning
confidence: 63%
“…In our previous study, 23 we have explored the sensitivity of the intrinsic tyrosine fluorescence to study insulin alterations and recovered the kinetics of its aggregation with the use of time-resolved emission spectroscopy (TRES). It has been found that hexameric insulin under physiological conditions undergoes conformational changes throughout 700 h. This was further supported by similar assembly kinetics of a model fibrillar protein, 24 suggesting a generic mechanism, and the sufficient sensitivity of TRES spectra to monitor protein stability for medicinal purposes.…”
Section: Introductionmentioning
confidence: 72%